2021
DOI: 10.1111/plb.13374
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of hydrogen sulphide and silicon enhance drought and heat tolerance by modulating hormones, antioxidant defence enzymes and redox status in barley (Hordeum vulgare L.)

Abstract: Recent changes in climate have reduced crop productivity throughout much of the world. Drought and heat stress, particularly in arid and semi‐arid regions, have seriously affected barley production. This study explored the separate and interactive effects of silicon (Si) and hydrogen sulphide (H2S) on plant growth and mitigation of the adverse effects of heat stress (DS) and drought stress (HS) in a barley pot experiment. The impacts of simultaneous DS + HS were more severe than individual stresses due to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…The majority of the definitions of cognitive engagement are drawn from two types of literature. One is their mental dedication to education, their desire to go above and beyond what is expected of them in school, and their demonstration that they embrace challenges; it is generally recognized as an important factor in determining the success of learning experiences (Batool et al, 2022Salameh et al, 2022;Tufail et al, 2022;Naz et al, 2022). This idea of cognitive involvement includes adaptability in problem-solving, a preference for diligence, and useful coping mechanisms in case of failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of the definitions of cognitive engagement are drawn from two types of literature. One is their mental dedication to education, their desire to go above and beyond what is expected of them in school, and their demonstration that they embrace challenges; it is generally recognized as an important factor in determining the success of learning experiences (Batool et al, 2022Salameh et al, 2022;Tufail et al, 2022;Naz et al, 2022). This idea of cognitive involvement includes adaptability in problem-solving, a preference for diligence, and useful coping mechanisms in case of failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mfarrej et al (2022) studied the response to H 2 S and NO in wheat under waterlogging stress and reported that both treatments alleviate waterlogging stress in wheat genotypes and improve the accumulation of essential nutrients and photosynthetic attributes and also regulate expression of stress-related genes. Naz et al (2022) reported that exogenous application of silicon (Si) with H 2 S was more effective in mitigation of drought and heat stress by modulating hormones, antioxidant defence enzymes and redox status in barley (Hordeum vulgare L.). Siddiqui et al (2022) reported that H 2 S significantly protects the quality of banana fruits after harvest by inhibiting oxidative damage, rapid ripening and senescence; H 2 S delays chlorophyll degradation and suppresses ethylene and CO 2 production.…”
Section: Emerging Role Of Hydrogen Sulphide As a Signalling Molecule ...mentioning
confidence: 99%
“…Naz et al . (2022) reported that exogenous application of silicon (Si) with H 2 S was more effective in mitigation of drought and heat stress by modulating hormones, antioxidant defence enzymes and redox status in barley ( Hordeum vulgare L.). Siddiqui et al .…”
mentioning
confidence: 99%
“…According to Wahid et al 19 , high temperatures can be accompanied by drought due to rapid water evaporation from the plant and soil surface. High temperature and drought stress have been studied in a variety of plant species, including wheat 20 , barley 21 , maize 22 , chickpea 23 , lentil 24 and soybean 25 . However, the combined effects of high temperatures and drought on plant growth, productivity and quality are more severe than the individual effects, with the reproductive phase being more vulnerable than the vegetative stage 26 .…”
Section: Introductionmentioning
confidence: 99%